Calcium phosphate nanocapsule crowned multiwalled carbon nanotubes for pH triggered intracellular anticancer drug release - Banerjee, Shashwat S.; Todkar, Kiran J.; Khutale, Ganesh V.; Chate, Govind P.; Biradar, Ankush V.; Gawande, Manoj B.; Zboril, Radek; Khandare, Jayant J. (Journal of Materials Chemistry B, 2015)
We report calcium phosphate (CaP) nanocapsule crowned multi-walled carbon nanotubes (CNT-GSH-G4-CaP) as a novel platform for intracellular delivery of an anticancer drug. As a proof-of-concept, CNT-GSH-G4-CaP demonstrates release of anticancer drug doxorubicin hydrochloride (DOX) within intracellular lysosomes from the interior cavity of CNT upon pH triggered CaP dissolution. Importantly, we found that the CNT with a CaP nanolid can efficiently prevent untimely drug release at physiological pH but promotes DOX release at increased acidic milieu as observed in subcellular compartments such as lysosomes (similar to 5.0). This ``zero premature release'' characteristic is of clinical significance in delivering cytotoxic drugs, by reducing systemic toxicity and thus beneficial for the effective anticancer treatment. We envision that this pH triggered CaP crowned CNT nanosystem would lead to a new generation of self-regulated platforms for intracellular delivery of a variety of anticancer drugs.

Core-shell nanoparticles: synthesis and applications in catalysis and electrocatalysis - Gawande, Manoj B.; Goswami, Anandarup; Asefa, Tewodros; Guo, Huizhang; Biradar, Ankush V.; Peng, Dong-Liang; Zboril, Radek; Varma, Rajender S. (Chemical Society Reviews, 2015)
Core-shell nanoparticles (CSNs) are a class of nanostructured materials that have recently received increased attention owing to their interesting properties and broad range of applications in catalysis, biology, materials chemistry and sensors. By rationally tuning the cores as well as the shells of such materials, a range of core-shell nanoparticles can be produced with tailorable properties that can play important roles in various catalytic processes and offer sustainable solutions to current energy problems. Various synthetic methods for preparing different classes of CSNs, including the Stober method, solvothermal method, one-pot synthetic method involving surfactants, etc., are briefly mentioned here. The roles of various classes of CSNs are exemplified for both catalytic and electrocatalytic applications, including oxidation, reduction, coupling reactions, etc.

Heterogeneously catalyzed strategies for the deconstruction of high density polyethylene: plastic waste valorisation to fuels - Burange, Anand S.; Gawande, Manoj B.; Lam, Frank L. Y.; Jayaram, Radha V.; Luque, Rafael (Green Chemistry, 2015)
The plastic industry generates enormous quantities of plastics at projected rates (both production and consumption) which can significantly threaten our environment in terms of plastic waste generation. High density polyethylene (HDPE) is one of the main fractions of municipal solid waste which has a remarkable potential to be valorised into fuels (e.g. bio-oils). Catalytic degradation is an innovative alternative process to transform plastic waste into such value added products. This mini review was aimed to discuss the most relevant and recent catalysts developed for the catalytic degradation of HDPE including metal oxides, sulphated metal oxides, zeolites, nanostructured zeolites, molecular sieves, fluid catalytic cracking (FCC) catalysts, metal carbonates and mesoporous materials for the production of chemicals and fuels (e.g. diesel and gasolines). Activities and selectivities as well as important effects of additives, particle size, catalyst to polymer ratios and also recent approaches for waste management will be discussed.

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP